COVID‐19 pandemic and economic scenarios for Ontario. (17th February 2022) - Casares, Miguel; Gomme, Paul; Khan, Hashmat
Abstract: To study the efficacy of the public policy response to the COVID‐19 pandemic, we develop a model of the rich interactions between epidemiology and socioeconomic choices. Preferences feature a "fear of death" that lead individuals to reduce their social activity and work time in the face of the pandemic. The aggregate effect of these reductions is to slow the spread of the novel coronavirus. We calibrate the model, including public policies, to developments in Ontario in the spring of 2020. The model fits the epidemiological data quite well, including the second wave starting in late 2020. We find that socioeconomic interventions work well in the short term, resulting in a rapid drop‐off in new cases. The long run, however, is governed chiefly by health developments. Welfare cost calculations point to synergies between the health and socioeconomic measures. Résumé: Pandémie de COVID‐19 et scénarios économiques en Ontario . Afin d'étudier l'efficacité des réponses de politiques publiques à la pandémie de COVID‐19, nous avons développé un modèle axé sur les interactions complexes entre les choix épidémiologiques et socio‐économiques. Face à la pandémie, les choix se caractérisent par une « peur de la mort » conduisant les individus à réduire leurs activités sociales et leur temps de travail. L'effet global de ces « limitations » vise à réduire la propagation du coronavirus. Nous avons calibré ce modèle, notamment les politiques publiques, à la situation épidémiologique et économique de l'Ontario au printemps 2020. Le modèle s'ajuste assez bien aux données épidémiologiques, y compris pour la seconde vague du virus fin 2020. Nous constatons que les interventions socio‐économiques sont efficaces à court terme, avec pour conséquence une diminution rapide du nombre de cas. En revanche, le long terme dépend essentiellement de l'évolution sanitaire. En matière de bien‐être, le calcul des coûts souligne les synergies entre les mesures sanitaires et économiques.